Two new species of the marine water mite family Pontarachnidae (Acari: Hydrachnidia) from the Gulf of Antalya, Turkey - Durucan, Furkan; Chatterjee, Tapas; Pešić, Vladimir (Zootaxa, 2018)
Two new species of the marine water mite family Pontarachnidae, i.e., Litarachna enigmatica and L. antalyaensis are described from the Gulf of Antalya, Turkey. Litarachna enigmatica is unique in the postgenital sclerite having a pair of so-called wheel-like acetabula, a character so far found only in the females of Pontarachna. Litarachna antalyaensis is the second known species of the L. duboscqi—species group characterized by the absence of a ventral tubercle on P-2 and presence of a ventral tubercle on P-4, from the Mediterranean Sea. The new species can be separated from the widely distributed L. duboscqi in the glandularium-like structure posterior to the fourth coxal plates not fused with adjoining coxoglandularia 4.